Fuentes de financiamiento y el desarrollo de los microempresarios del mercado artesanal de San Juan, 2021 - Piña Cordova, Maria Laura de Jesus (2022)
The present investigation had as general objective to determine the relationship between the sources of financing and the development of the microentrepreneurs of the Artisan Market of San Juan, year 2021; opting for an applied research, of a descriptive correlational level and non-experimental design, for which a sample of 50 microentrepreneurs has been taken, who were surveyed through a questionnaire that analyzes their perception regarding the variables evaluated; managing to conclude that the contribution of the owner as a source of financing is regularly and significantly related to the development of the microentrepreneurs participating in the research. Likewise, there is a considerable and significant relationship between commercial sources and the development of microentrepreneurs. On the other hand, financial sources are considerably and significantly related to the development of microentrepreneurs, since when making a loan it would be with the objective of investing it. In addition, it was determined that there is a considerable and significant relationship between financing by third parties and the development of microentrepreneurs, that is, financing by third parties also has an impact on development. Finally, it was determined that the sources of financing are considerably and significantly related to the development of the microentrepreneurs of the San Juan Artisan Market during 2021.